The Role of Principal Curriculum Leadership in the Success of Technology-Based Curriculum Innovation: A Mixed-Methods Study - Zulfiqar Syafiq; Mughni Mughni; Dhiya Dhiya (Institute of Accounting Research and Novation (IARN), 2025)
Technology-based curriculum innovation has become increasingly important in responding to changes in teaching, learning, and digital competencies. However, successful implementation depends not only on technological infrastructure but also on school leadership capable of aligning technology with curriculum objectives and supporting teachers through organizational change. This study aims to examine the role of principals' curriculum leadership in the successful implementation of technology-based curriculum innovation and to identify leadership practices that facilitate sustainable curriculum transformation. The study employed an explanatory sequential mixed-methods design involving 300 teachers from schools implementing technology-based curriculum innovation. Quantitative data were collected using a structured five-point Likert-scale questionnaire measuring principal curriculum leadership, teacher readiness, teacher digital competence, technology integration, and innovation success. Quantitative data were analyzed using descriptive statistics and PLS-SEM, while qualitative data were obtained through semi-structured interviews and document analysis and analyzed thematically. The findings indicate that principal curriculum leadership was high (M = 4.18, SD = 0.48) and had a positive and significant effect on technology-based curriculum innovation success (β = 0.612, t = 11.284, p < 0.001), explaining 52.8% of its variance (R² = 0.528). Teacher digital competence partially mediated this relationship (indirect effect = 0.309, p < 0.001). Qualitative findings identified strategic vision, teacher empowerment, resource provision, change management, and continuous monitoring as key leadership practices. Principal curriculum leadership plays a critical role in transforming technology adoption into sustainable curriculum innovation. Successful implementation requires strategic leadership, teacher empowerment, adequate resources, organizational support, and continuous evaluation.